Model of Peacock Tail Covert Feather Based on Its Microscopic Structure - Vilasineewan*, Chinawat; Siripant, Suchada; Meckvichai, Wina (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
This article presents a mathematical model called “the ridge model”, which is used to create peacock tail covert feathers based on the relationships among the morphological data. A feather consists of diverse microscopic structures that include the rachis, barbs and barbules, which can, in modeling terms, be represented by curves. In this research, the Bezier curve is used. The methods used to generate the colour patterns of peacock tail covert feathers, which can be applied to feathers with similar features from different species, are developed and presented. Keywords: Feather modeling, Rendering, Computer Graphics E-mail: kyaoga@yahoo.com